The Privacy-Centric Data Pipeline : Strategies for Implementing Robust Security Measures in Data Engineering - Pradeep Kumar Sekar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive framework for addressing data privacy and security challenges in modern data engineering environments. As organizations grapple with ever-increasing volumes of sensitive data and an evolving regulatory landscape, data engineers face complex challenges in safeguarding information throughout its lifecycle. We explore key components of a robust data protection strategy, including regulatory compliance, technical safeguards, and organizational practices. Our analysis covers critical areas such as encryption methodologies, access control mechanisms, data masking techniques, and lifecycle management policies. We also examine the role of data governance frameworks and the importance of continuous employee training in maintaining a secure data ecosystem. By synthesizing current best practices and emerging trends, this article provides data engineers and organizations with actionable insights for implementing effective privacy and security measures. Our findings underscore the need for a holistic approach that integrates technical solutions with strong governance practices to ensure data integrity, confidentiality, and compliance in an increasingly data-driven world.
Keywords: Data Privacy; Cybersecurity; Data Engineering; Regulatory Compliance; Data Governance